Development, reproduction and longevity of Aprostocetus sp. (Hymenoptera: Eulophidae), an egg parasitoid of the Brown planthopper, Nilaparvata lugens (Stål) (Hemiptera: Delphacidae) - Vongpa, Vilaivan; Amornsak, Weerawan; Gordh, Gordon (Agriculture and Natural Resources, 2016)
Aprostocetus sp. (Hymenoptera: Eulophidae) is an egg parasitoid of Nilaparvata lugens (Stål) (Hemiptera: Delphacidae). This parasitoid was surveyed and collected from paddy fields in Nonthaburi and Pathum Thani provinces, Thailand. Aprostocetus sp. was reared on N. lugens eggs under laboratory conditions at the National Biological Control Research Center, Kasetsart University, Bangkok, Thailand. The development time, reproductive performance and adult longevity of Aprostocetus sp. were investigated. The development time of Aprostocetus sp. took 12-19 d; the mean development time of female and male wasps was 15.4 ± 1.3 and 14.8 ± 1.3 d, respectively. The mean daily offspring production was 3.5 ± 0.6 wasps; total offspring production was 74.7 ± 33 wasps; and the sex ratio (female to male) was 1.8:1. The longevity of adult female wasps fed with honey and without honey was 5.3 ± 0.88 and 1.9 ± 0.14 d, respectively. The longevity of adult male wasps fed with honey and without honey was 1.9 ± 1.2 and 1.4 ± 0.5 d, respectively. The longevity was significantly (p < 0.05) different between food sources for both females and males.